CFAP43 variant in persistent respiratory symptoms after hematopoietic cell transplantation - Shun Nagasawa; Toyoki Nishimura; Ai Yamada; Sachiyo Kamimura; Masataka Ishimura; Hiroshi Moritake (Human Genome Variation)
Abstract We describe a case of RAS-associated autoimmune leukoproliferative disease with primary ciliary dyskinesia (PCD)-like symptoms, such as recurrent pneumonia, sinusitis, and otitis media, that occurred 7 years after hematopoietic cell transplantation. Whole-exome sequencing revealed a heterozygous CFAP43 nonsense variant. Environmental factors related to hematopoietic cell transplantation may have led to PCD symptoms in this patient with this variant. Genetic screening can help avoid subsequent complications during patient management.